Implementing Pancasila Student Profiles in Elementary Schools - Nida Ul’ Husna Rabbani; Elsih Yulian Nisah; Siska Nur Fadillah (CV. Rayyan Dwi Bharata, 2023)
The profile of Pancasila students is part of the Ministry of Education and Culture's vision and mission, which is very important to do in educational institutions, to grow and develop students as Pancasila students, who show the value of faith, fear of God Almighty and have noble character, critical thinking, global diversity, mutual cooperation , independent, and creative. The role of Pancasila students here is very important to shape the personality of students, must develop their intelligence after graduation, and cultivate their attitude and intellect. Pancasila is the basic ideology of the Indonesian state, its name is composed of Sankskrit: Panca means five, and sila means principle or principles. The profile of Pancasila students is the main goal carried out by educational developers, the purpose of education is to produce a superior and intelligent generation and have noble morals. Education can drive change to be better than the previous generation. It is also through education that the Indonesian people are able to give birth to a generation that is creative, innovative, problem solving and productive to build the nation. The purpose of this research is to describe various implementations with patterns of strategies and methods applied by teachers in realizing the profile of Pancasila students. The role of the teacher here is to shape the character of students, whose role here is not only the teacher but also the family and social environment. This type of research uses the method of literature review, the theory or basis of this discussion is obtained from the results of obtaining information from many parties such as books, journals and articles. This research is to implement Pancasila values in life, namely the application of Pancasila is very important to be formed by students including elementary school children, human quality, good attitudes and behavior to improve the quality of Indonesian education.